1999
DOI: 10.1083/jcb.144.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-dependent Control of Translation: Engagement of Integrin αIIbβ3 Regulates Synthesis of Proteins in Activated Human Platelets

Abstract: Integrins are widely expressed plasma membrane adhesion molecules that tether cells to matrix proteins and to one another in cell–cell interactions. Integrins also transmit outside-in signals that regulate functional responses of cells, and are known to influence gene expression by regulating transcription. In previous studies we found that platelets, which are naturally occurring anucleate cytoplasts, translate preformed mRNA transcripts when they are activated by outside-in signals. Using strategies that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
3
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 74 publications
5
123
3
4
Order By: Relevance
“…Several integrins, including ␣ 6 ␤ 4 , ␣ IIb ␤ 3 , and ␣ 2 ␤ 1 , can promote translation of weak mRNAs through the PI3K-Akt-mTOR pathway (31,32). In contrast, activation of integrin ␣ v ␤ 3 did not result in enhanced activation of mTOR or Akt in brain lesions, suggesting that a different mechanism is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several integrins, including ␣ 6 ␤ 4 , ␣ IIb ␤ 3 , and ␣ 2 ␤ 1 , can promote translation of weak mRNAs through the PI3K-Akt-mTOR pathway (31,32). In contrast, activation of integrin ␣ v ␤ 3 did not result in enhanced activation of mTOR or Akt in brain lesions, suggesting that a different mechanism is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of adhesion on translation were described for other substrates (27)(28)(29) showing the importance of mTOR and eIF4E relocalization. We found that FN induces translation through eIF4F with a marginal involvement of the mTOR pathway, and, consistently, without stimulating TOP mRNA translation (see model in Fig.…”
Section: Pi3k Activation Does Not Restore Translation In Attachment-dmentioning
confidence: 99%
“…The effect of adhesion to ECM on translation has been addressed in models requiring ␤3 integrin (27,28) or ␤4 integrin (29) and in platelets (30). These studies showed the importance of the activation of mTOR in adhesion-regulated translation.…”
mentioning
confidence: 99%
“…[66][67][68][69] Upregulated cap-dependent translation liberates cells from strict dependence on adhesion. For example, ectopic eIF4E converts immortalized HMECs into cells that form colonies when cultured at low density on a plastic substratum or in soft agar, 57 but does not by itself enable tumorigenicity.…”
Section: Translational Control Of Malignant Conversionmentioning
confidence: 99%